관경 변화에 따른 R-1234yf의 응축 압력강하에 관한 실험적 연구 - 손창효(Chang-Hyo Son) (동력시스템공학회지, 2021)
본 연구에서는 관경 변화에 따른 R-1234yf의 응축 압력 강하를 실험적으로 연구하여 응축기 설계의 기초 자료로 제공하고자 한다. 실험은 질량 유속, 포화 온도 및 관경을 변경하며, R-1234yf의 압력 강하를 측정했다. 그리고 동일한 조건에서 R-134a의 압력 강하와 비교했다. 그 결과, 질량 유속이 증가하고 관경이 감소함에 따라 압력 강하는 증가하는 경향이 나타났다. 그리고 포화 온도가 증가함에 따라 압력 강하는 감소하는 경향을 보였다. 실험결과와 R-134a의 압력 강하를 비교한 결과, R-134a가 R-1234yf보다 큰 경향을 보였다. 실험결과를 기존 상관식과 비교한 결과 Miyara 등의 상관식이 가장 유사한 예측을 보였다. In this study, the condensation pressure drop of R-1234yf according to the variation of the tube diameter is experimentally studied and it is intended to be provided as the basic data for the design of the condenser. The experiment measured the pressure drop of R-1234yf by changing the mass flow rate, saturation temperature, and tube diameter. It also compared with the pressure drop of R-134a under the same conditions. As a result, the pressure drop tends to increase as the mass flow rate increases and the tube diameter decreases. In addition, the pressure drop tends to decrease as the saturation temperature increases. As a result of comparing the experimental results and the pressure drop of R-134a, R-134a showed a larger tendency than R-1234yf. As a result of comparing the experimental results with the existing correlation equation, the correlation equation of Miyara et al showed the most similar prediction. KCI Citation Count: 0